Phthalocyanine-based bio-functional conjugates: photodynamic therapy and photoantimicrobial chemotherapeutic efficacy evaluation in-vitro - Magadla, Aviwe (Rhodes University, Faculty of Science, Department of Chemistry)
This thesis reports on the syntheses and characterisation of symmetrical and asymmetrical phthalocyanines (Pcs) with different ring substituents derived to form either cationic styryl pyridine, cationic styryl pyridine triphenylphosphonium (TPP+)-based, benzothiazole, cationic pyridyl-dihydrothiazole and other closely related groups. The starting Pc complex of the synthesised Pc derivatives was typically obtained through the cyclotetramerisation of a substituted phthalonitrile. Then, depending on the desired final complex, the desired complexes were synthesised through the Knoevenagel condensation, alkylation reaction, and Schiff base reaction. Furthermore, silica nanoparticles (SiNPs) were also used to encapsulate Pcs. Following aminopropyl triethoxysilane amino (APTES) functionalisation of the surface of the Pc@SiNPs-APTES, biomolecules such as gallic acid, folic acid, and ampicillin were covalently attached to the surface. Additionally, Pc@SiNPs-APTES is protonated with 1,3-propanesultone. The pair of synthesised asymmetric Pcs is attached to ciprofloxacin (CIP) via an amide bond. Different analytical methods were used to characterise the Pcs and their conjugates. The photophysics and photochemistry of the Pcs both by themselves and in their conjugate form when doped with SiNPs. The cationic Pcs were able to produce sufficient singlet oxygen on their own in most cases. This is explained by the Pcs greater solubility in water. Since singlet oxygen is produced from the triplet state, singlet oxygen quantum yield (ï †Î”) values complement triplet quantum yield (ï †T) values. Low ï †Î” values could be attributed to ineffective energy transfer; screening effects may have prevented the excited triplet state of the Pcs from interacting with the ground state molecular oxygen, lowering the ï †Î” values. In other instances, the Pcs' protection by the SiNPs could be credited with extending the triplet lifetime. The direct connection of Pcs with CIP increased the formation of ï †T and ï †Î” in ABSTRACT comparison to Pcs alone. Both in planktonic and biofilm form, the cationic Pcs and conjugates showed enhanced bacterial elimination. The Pcs and conjugates demonstrated significant activity in photodynamic therapy treatment (PDT) experiments at the tested doses. In both PDT and photodynamic antimicrobial chemotherapy (PACT) treatment, the cationic Pcs outperformed the neutral Pc in terms of biological activity.
Keywords: Photochemotherapy; Anti-infective agents; Biofilms; Active oxygen; Quantum yield; Phthalocyanines